Performance of Kappaphycus alvarezii Seaweed from Maumere and Tembalang in Longline System Cultivation - Fadli Zainuddin; M. Masyarul Rusdani (Airlangga University, 2018)
The Kappaphycus alvarezii seaweed widely cultivated originates from Maumere and Tembalang. Kappaphycus alvarezii has a high economic value because of the high carrageenan content used in food products, cosmetics, and medicines. This research was evaluated the performance of seaweed (Maumere and Tembalang) cultivated using longline method near to the shore. Research was conducted by cultivating seaweed using lines extending 50 m long, of each 2 ropes for Maumere seaweed and the other 2 ropes for Tembalang, and then the seaweeds were cultivated for 45 days. Daily control and sampling were conducted to determine the performance of seaweed every 15 days as well as water sampling was taken to determine the water quality of the cultivation location. The results showed that Maumere seaweed performance was higher than Tembalang seaweed and that the water quality was suitable for seaweed cultivation. Keywords: Performance, Kappaphycus alvarezii, Tembalang, Maumere